Low Seroconversion after One Dose of AS03-Adjuvanted H1N1 Pandemic Influenza Vaccine in Solid-Organ Transplant Recipients - Mariangela R Resende; Shahid Husain; Jonathan Gubbay; Lianne Singer; Edward Cole; Eberhard L Renner; Coleman Rotstein (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Immunocompromised individuals are more susceptible to complications produced by influenza infection. As a result, solid-organ transplant (SOT) recipients were targeted as a priority group to receive AS03-adjuvanted H1N1 influenza vaccine during 2009.